Sesar's ATM Target Concept: Keys to sucess. - Brooker, Peter (Cranfield University, 2008)
There is often a right time to do things. In the 1570s, Martin Frobisher abandoned his efforts to find the Northwest Passage, but the attempt might well have been successful today. The nature of a problem and the technical tools available to tackle it can change dramatically over time. Is this the right time for radical changes to Air Traffic Management (ATM)? What will be the keys to success? An earlier article in Navigation News (Jan/Feb 2007) examined the USA’s Air Traffic Management (ATM) programme NGATS, now renamed ‘NextGen’. There has recently been important progress in the European analogue to NextGen: SESAR. SESAR is the European ATM modernization programme, focused on 2020. Its first phase is the Definition Phase, which is co-funded by Eurocontrol and the European Commission (Trans European networks). The SESAR Consortium is carrying out the Definition Phase study. The Consortium has about 30 members (eg Air France, BAE Systems) and about 20 associated partners (eg Boeing, Dassault, and European ATM research centres). A major ‘SESAR Deliverable’ was the 162-page ‘ATM Target Concept’, issued in late September 2007. This briefing paper illustrates some of the important features of the Concept, especially where its ‘magic’ might come from to deliver large improvements in performance, and tries to identify key issues in the path to successful implementation. The report’s authors make it very clear that it is a vision not a plan, and certainly not a final blueprint of the future system.